Development of a Catch-Throwing Skill Analyzer Based on Sensors - Komaini, Anton; Kiram, Yanuar; Razi, Pakhrur; Zakaria, Jaffri Bin; Handayani, Sri Gusti; Andika, Heru (Society of Visual Informatics, 2024)
This research aims to develop a tool for measuring catching-throwing skills using modern, effective, and efficient sensor technology. This tool is designed to increase accuracy in measuring catch-throwing skills. This type of research uses (R&D). This research involved three experts in their field: an electrical expert, an evaluation and measurement expert, and a physicist. A total of 30 participants participated in testing in a small group of 12 people and a large group of 18 people with an age range of 15-20 years. Testing is carried out with questionnaires and direct tests. The statistical analysis used is r-correlation with the help of the SPSS application. The test results show a high alpha coefficient, confirming that this tool is consistent and reliable in collecting data. Three experts carried out practicality testing: Electrical Experts, Evaluation and Measurement Experts, and Physicists. The results show that this tool is efficient, with practicality levels of 98%, 92%, and 89%, respectively. In addition, an excellent level of effectiveness is demonstrated by expert assessment results, which reach 99%, 89%, and 85%. With this tool, researchers and teachers can evaluate object control skills more efficiently and accurately and assist in collecting more comprehensive data. Overall, this tool for measuring throwing and catching skills provides significant innovation and is expected to support research and education in measuring and developing children's motor skills.